The Greek hero Perseus : myths of maturation - Dillon, JEM (1989)
Owing to a certain fascination with the Gorgon and its origins, past scholarship has given less consideration to Perseus as a heroic figure in his own right than might be expected. He is generally thought of as colourless in comparison with heroes such as Heracles, Theseus and Jason. As a body, his myths have in any case received little attention in the last thirty years, and the thesis attempts to redress the balance, to ‘parse’ Perseus by ‘construing’ his myths. He is indispensable to all the myths. The initiatory schema, in terms both of a general rite of passage, and more specifically of ‘ephebic’ motifs, is central, and is established in the introductory chapter (I). The movement of the hero from οικος to πολις, is coextensive with his maturation. The remaining chapters (II-V), on Acrisius, the Gorgon, Andromeda and Dionysus, follow through the process of Perseus’ maturation, from his anomalous birth, exposure, his youthful exploits, acquisition of a wife, to his return to and defence of the πολις, Argos, from Dionysus and his θιασος. He returns to Argos with divine sanction despite all mortal attempts to prevent him: the preservation of the οικος, and by extension the πολις, is key to the characterization of Perseus. His myths are a particularly potent example of the tendency, and imperative for, Greek values of civilization, as represented by the οικος and πολις, to be perpetuated. In this sense, Perseus is a ‘political’ hero. An appendix on the fragmentary Perseus dramas performed in antiquity confirms his popularity throughout the whole of the fifth century and beyond, and shows that, contrary to what the relatively skeletal sources might suggest, he was not simply a cipher, but a fully characterized figure in the Greek imagination.